Chemo-enzymatic epoxidation of 1-nonene, 1-heptene and styrene - Arumugam, Mahashanon (2013)
In view of the emerging importance of enzyme as a promising biocatalyst in fine organic synthesis, we focused on the synthesis of epoxides for their potential applications in chiral synthesis, including asymmetric synthesis and optical resolution of racemates. Epoxides are increasingly used as intermediates in many industrial processes and have wide applications in food, polymer and pharmaceutical formulations due to their excellent ability to facilitate ring opening reactions to various desirable functional groups. The enzymatic synthesis of epoxides has received much attention for its clean production due to its high-regioselectivity and low production of by-products. Furthermore, hydrogen peroxide (H2O2) as green oxidant and mild operating temperature, hence, low energy requirement, are becoming two important advantages of this enzymatic reaction. Herein, we describe an improved enzyme-facilitated epoxidation of a simple alkene (1-nonene) using a conventional water bath shaker. The lipase was used to catalyse the formation of peroxy acids instantly from H2O2 and various perhydrolysis substrates. The peroxy acid generated was then utilised directly for in-situ oxidation of 1-nonene to 1-nonene oxide. Various reaction parameters affecting the synthesis of epoxide, including the nature of peroxy acids, organic solvents, enzyme’s sources, enzyme concentrations, reaction temperatures, initial concentrations and rate additions of the H2O2, stirring rates (rpm), and amounts of H2O2 and peroxy acid, were investigated. Highest conversion was achieved using phenylacetic acid as an oxygen carrier. 1-nonene was converted most efficiently with maximum yield of 97% by Novozym 435, an immobilised Candida antarctica lipase B (CALB) and chloroform as reaction media. A minimum amount (1.4% w/w, 19 mg) of Novozym 435 was needed to maintain the catalytic activity (190.0 Ug-1). The highest yield was successfully obtained within 12 h reaction time at optimal synthesis conditions (35°C, 4.4 mmol of H2O2 (30%) in a single step addition, stirring rate 250 rpm and 8.8 mmol of phenylacetic acid). Subsequently, the optimised conditions were employed for the epoxidation of an array of aliphatic (1-heptene) and aromatic (styrene) alkenes which gave 94% to 99% yield and quantitative purity. In addition, a simple and rapid gas chromatography – mass spectrometry (GC-MS) selective ion monitoring (SIM) method was developed using an HP-5ms column for determining the epoxide yields. For 1-nonene oxide, the method was found to be linear in the range of 29.9 - 298.8 mg/L with R2 = 0.9960.